ADAPTIVE BREASTFEEDING SUPPORT TECHNIQUES FOR MOTHERS WITH DISABILITIES - Astuti, Siti Choirul Dwi; Magdalena M. Tompunuh; Puspita Sukmawaty Rasyid (Journal of Applied Health Management and Technology, 2025)
Breastfeeding is recommended because of its many benefits for both mother and baby. For mothers who have limitations breastfeeding, breastfeeding is difficult to do but also not impossible to do. The purpose of this study is to identify breastfeeding techniques used by mothers who have physical limitations based on existing literature. Literature search methods were conducted on scientific sites such as ScienceDirect, Pubmed, Elsiver, NCBI, DOAJ, Proquest, Microsoft Academic, Sage Journal, Oxford Academic, LIPI, ResearceGate, JSTOR and Scrib.id using the keywords breastfeeding and disability.Â  The search results obtained 234 articles but only 7 articles were used and described breastfeeding techniques for mothers with disabilities and other articles that were eliminated were not used because they did not describe breastfeeding techniques for mothers with disabilities. This article presents a literature review on breastfeeding techniques in mothers with disabilities. Breastfeeding is one of the best ways to provide nutrition to babies, but mothers with disabilities often face additional challenges that can affect their ability to breastfeed effectively. In this article, various relevant studies and research are analyzed to identify the challenges, needs, as well as solutions that have been developed to support mothers with disabilities in the breastfeeding process. The main focus of this review is on specific techniques that can make it easier for mothers with physical or cognitive disabilities to breastfeed, including the use of assistive devices, modification of breastfeeding positions, and the role of social and medical support. These findings demonstrate the importance of an inclusive and personalized approach to providing support to mothers with disabilities, as well as the need for more responsive health policies to ensure equal access to maternal health services. This article also underlines the need for further research to develop practical guidelines that can be applied in a variety of contexts.